2016
DOI: 10.1103/physreva.93.052306
|View full text |Cite
|
Sign up to set email alerts
|

Probing anharmonicity of a quantum oscillator in an optomechanical cavity

Abstract: We present a way of measuring with high precision the anharmonicity of a quantum oscillator coupled to an optical field via radiation pressure. Our protocol uses a sequence of pulsed interactions to perform a loop in the phase space of the mechanical oscillator, which is prepared in a thermal state. We show how the optical field acquires a phase depending on the anharmonicity. Remarkably, one only needs small initial cooling of the mechanical motion to probe even small anharmonicities. Finally, by applying too… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 52 publications
(87 reference statements)
0
23
0
Order By: Relevance
“…For systems operating in the nonlinear regime, the quantum Fisher information (QFI) for measurements of constant gravitational acceleration has already been computed [25,26], and optimal estimation schemes for the nonlinear coupling itself have been considered [27]. In general, the estimation of anharmonicities present in the system is a topic of great interest [28,29] as well as the enhancement of parameter estimation granted by Kerr nonlinearities [30,31]. Additional efforts have focused on parametric driving of the cavity frequency, which manifests itself as a single-mode mechanical squeezing term in the Hamiltonian [32].…”
Section: Introductionmentioning
confidence: 99%
“…For systems operating in the nonlinear regime, the quantum Fisher information (QFI) for measurements of constant gravitational acceleration has already been computed [25,26], and optimal estimation schemes for the nonlinear coupling itself have been considered [27]. In general, the estimation of anharmonicities present in the system is a topic of great interest [28,29] as well as the enhancement of parameter estimation granted by Kerr nonlinearities [30,31]. Additional efforts have focused on parametric driving of the cavity frequency, which manifests itself as a single-mode mechanical squeezing term in the Hamiltonian [32].…”
Section: Introductionmentioning
confidence: 99%
“…This enhancement can be achieved, for example, by using a large-amplitude, strongly detuned mechanical parametric drive [45], or by modulating the spring constant [46]. Similar work has shown that the inclusion of a mechanical quartic anharmonic term can be nearly optimally detected with homodyne and heterodyne detection schemes, which are standard measurements implemented in the laboratory [47].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of optomechanical self-oscillations, a theoretical proposal has been made [35] to achieve the steady-state sub-Poissonian phonon statistics in an optomechanical cavity, by using the intrinsic anharmonicity of the mechanical oscillator. Furthermore, it has been recently proposed a protocol to estimate the anharmonicity of a quantum mechanical oscillator in an optomechanical cavity [36] in order to explore its contribution to the dynamics and its impact on the experimental results.…”
Section: Introductionmentioning
confidence: 99%